Botryosphaeriaceae fungi on apple fruit – identification and sensitivity to fungicides and essential oils in vitro - Milošević, Milica; Stepanović, Jelena; Rekanović, Emil; Stepanović, Miloš (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2025)
Apple production suffers significant economic losses and fruit quality reductiondue to fungal pathogens, particularly ones that cause postharvest fruit rot, such asBotryosphaeriaceae fungi. Isolates used in this study were obtained from symptomaticapples and, based on morphological characteristics and sequence analysis of two genes(EF 1-α and β-tubulin), they were identified as Diplodia seriata and Botryosphaeria dothidea.Pathogenicity tests on healthy apple fruits revealed that D. seriata was more aggressivethan B. dothidea, with significantly higher average values of lesion diameter and depth.Fungicide sensitivity tests showed that D. seriata was more sensitive to the combinationfluopyram + tebuconazole (EC50=0.00023 μg a.i. ml-1), while B. dothidea exhibited highersensitivity to pyraclostrobin (EC50=0.025 μg a.i. ml-1). With 98.44% and 97.56% percentgrowth inhibition (PGI) rate of D. seriata and B. dothidea (respectively) at 10 μg a.i. ml-1, thetested combination of fungicides surpassed pyraclostrobin in inhibition potential. Fouressential oils (thyme, rosemary, lavender and lemongrass) were also tested for antifungalactivity using the fumigant macrodilution method. Thyme oil demonstrated the highestantifungal potential, completely inhibiting the mycelial growth of both species at0.05 μl ml–¹ of air. Strong inhibition potential was also shown by lemongrass oil with100% inhibition of D. seriata and B. dothidea mycelial growth at 0.07 and 0.09 μl ml–¹ of air,respectively. Rosemary oil showed a moderate inhibition potential, while lavender oil wasthe least effective. These findings highlight the inhibiting potential of fungicides againstD. seriata and B. dothidea, but they also indicate that thyme and lemongrass essentialoils could be used as viable alternatives. Further research is needed to determine theireffectiveness in in vivo assays and potential impact on fruit quality and the environment.
Keywords: apple; fungal pathogens; postharvest fruit rot; fungicides; essential oils; antifungal activity